2021
DOI: 10.1108/aaaj-09-2020-4926
|View full text |Cite
|
Sign up to set email alerts
|

COVID-19 and the governmentality of emergency food in the City of Turin

Abstract: PurposeThis paper shows the accounting, accountability and calculative practices associated with emergency food allocations by the City of Turin through a program to feed the vulnerable during COVID-19.Design/methodology/approachThis is a single case study framed by Foucault's governmentality concept. The data was collected through interviews with key institutional actors and triangulated against decrees, circulars, ordinances and other publicly available documents.FindingsThe accounting tools of governmentali… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
13
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 17 publications
(14 citation statements)
references
References 17 publications
0
13
0
Order By: Relevance
“…According to their findings, this method allows shared responsibility and benefits for municipal councils, businesses, and households for recyclable commodities, leading to the lowest waste costs and creating economic, social, and environmental benefits for households. An accounting perspective was also adopted by Sargiacomo et al (2021), who showed the accounting, accountability, and calculative practices associated with emergency food allocations by the City of Turin through a program developed amidst COVID-19. Their findings suggested that the accounting tools of governmentality are always incomplete.…”
Section: Performance and Measurement Systemsmentioning
confidence: 99%
“…According to their findings, this method allows shared responsibility and benefits for municipal councils, businesses, and households for recyclable commodities, leading to the lowest waste costs and creating economic, social, and environmental benefits for households. An accounting perspective was also adopted by Sargiacomo et al (2021), who showed the accounting, accountability, and calculative practices associated with emergency food allocations by the City of Turin through a program developed amidst COVID-19. Their findings suggested that the accounting tools of governmentality are always incomplete.…”
Section: Performance and Measurement Systemsmentioning
confidence: 99%
“…Indeed, fundamental shift in decision-making practices that are rooted in organizational culture can be exceptionally challenging during the best of times and even more daunting in a time of crisis that often involves increased pressure on resources and enhances employee resistance (Bovey and Hede 2001;Bordia et al, 2006;Peters, Pierre, and Randma-Liiv 2011;Sargiacomo et al, 2021;Thelen 2000). Hence, our findings do not find significant change in decision-making methods and the associated data use during the COVID-19 pandemic (also see Thelen 2000).…”
Section: Discussionmentioning
confidence: 58%
“…Recognising that accounting presents information partially and has social and moral imperatives as well as technical applications (Carnegie et al , 2021a, 2021b), this study adopts a broad interpretation of accounting and, subsequently, of what constitutes “an account”. Similar to Sargiacomo et al (2012, p. 396), this study focuses on “an accounting” of and for the Newmarch House crisis, necessitating “alternative accounts that re-situate the human experience as worthy of inclusion and value” (Twyford, 2021, p. 354).…”
Section: An Accounting For Biopolitics In a Crisismentioning
confidence: 99%